Influence of Zingiber officinale extract on push - Out bond strength of glass-fiber post - da Silva, Tânia Mara [UNESP]; Fernandes Junior, Virgílio Vilas Boas [UNESP]; de Santana, Rosemary Soares [UNESP]; Marinho, Renata Marques de Melo [UNESP]; Valera, Márcia Carneiro [UNESP]; Bresciani, Eduardo [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this study was to evaluate in vitro the influence of 20% glycolic ginger extract on the bond strength of glass-fiber post cemented with etch-and-rinse or self-etching resin cement. Forty-eight bovine roots were standardized (17±0.5 mm) and randomly divided into two groups, according to irrigant used during biomechanical preparation: NaOCl: 1% sodium hypochlorite and GEN: 20% glycolic ginger extract. Root canal was prepared and randomly assigned to one of two subgroups (n=12), according to luting protocol: self-etching (RelyX U200) and etch-and-rinse (RelyX ARC). After 48 h, the roots were sectioned perpendicularly (4 in cervical third and 3 in middle third) and submitted to push-out bond strength test (50 kgf load cell, 1.0 mm/min). Failure mode was analyzed in SEM and stereomicroscopy. Data were analyzed by three-way ANOVA and Tukey tests (p<0.05). ANOVA revealed that there were no significant differences between U200 (2.01±0.17)B and ARC (1.93±0.12)B in GEN group, and at the cervical third for both irrigants, 2.69±0.16A and 2.54±0.17A, respectively. Middle third showed lower bond strength than cervical third, regardless the irrigant. Overall, the cervical third regardless the irrigant employed and the association between NaOCl and ARC, presented better adhesive performance.
Keywords: Adhesion; Luting agents; Post; Zingiber officinale